Performance Analysis of Electric Motorcycles as Logistics Vehicles - Rifki Dwi Putranto; Julia Putri Maharani; Darul Panji Khakiki; Ryan Nur Saputro; Afredo Oktaviano (Journal of Energy, Material, and Instrumentation Technology, 2026)
This study analyzes the performance of a 3000 W Brushless Direct Current (BLDC) motor implemented in the E-Ninja Tel-U Surabaya electric motorcycle, which was converted from a conventional motorcycle for logistics applications. The research focuses on evaluating energy consumption, motor efficiency, and vehicle performance under different operational conditions. Testing was conducted using a 72 V 24 Ah lithium-ion battery system with variations in speed ranging from 30–60 km/h and payloads of 100 kg and 150 kg. The analysis includes charging–discharging characteristics, traction force calculations, rolling resistance, aerodynamic drag, climbing force, and acceleration force. Electrical parameters such as voltage, current, power, and energy consumption were measured using a PZEM Energy Meter, while speed and travel distance were monitored through a GPS Speedometer application. The results show that higher vehicle speed and heavier payload significantly increase power consumption due to greater aerodynamic drag, rolling resistance, and motor workload. The most efficient operating condition was achieved at speeds of 30–40 km/h with the lowest energy consumption of 29.27 Wh/km. Increasing the load from 100 kg to 150 kg caused proportional growth in energy consumption because the motor required higher torque to maintain constant speed. In addition, the 72 V battery charging system with a 5 A charger demonstrated stable and efficient three-stage charging performance within approximately five hours. The findings indicate that BLDC-based electric motorcycle conversion is a feasible and sustainable transportation solution for logistics operations, supporting energy efficiency and the achievement of Sustainable Development Goals (SDGs) related to clean energy and carbon emission reduction.